2009
DOI: 10.1509/jmkr.46.5.584
|View full text |Cite
|
Sign up to set email alerts
|

Learning from a Service Guarantee Quasi Experiment

Abstract: We analyze data from a service guarantee program implemented by a mid-priced hotel chain. Using a multi-site regression discontinuity quasi-experimental design developed for these data from 85,321 guests and 81 hotels over 16 months, we control for unobserved heterogeneity among guests and treatments across hotels, and develop Bayesian posterior estimates of the varying program effect for each hotel. Our results contribute to theory and practice. First, we provide new insights into how service guarantee progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…This finding contradicts the proposed assumption that service guarantee will inspire the employees to deliver the expected standard of service quality. However, the findings is consistent with Chen et al's [26] study that found no significant relationship between both constructs.…”
Section: Resultssupporting
confidence: 90%
“…This finding contradicts the proposed assumption that service guarantee will inspire the employees to deliver the expected standard of service quality. However, the findings is consistent with Chen et al's [26] study that found no significant relationship between both constructs.…”
Section: Resultssupporting
confidence: 90%
“…Customers have an incentive to play to earn the reward when their current score is below the cutoff, but a reduced incentive to play with the objective of earning a reward when their current score already exceeds the cutoff. 5 As before, we consider a two-stage model. In the first stage, the consumer makes a selection decision.…”
Section: Setupmentioning
confidence: 99%
“…Another stream that emerges focuses on a topic noted as important but understudied by Hogreve and Gremler (2009), which is research examining the business outcomes and return on investment that companies can gain from offering a service guarantee. For example, such research has focused on the experiences companies actually have had designing and launching service guarantees and the difficulties encountered (McColl and Mattsson 2011;Chen et al 2009) and the effect of service guarantees on business outcomes including market value (Meyer, Gremler, and Hogreve 2014;Shin and Ellinger 2013). Even with a continuously steady stream of research being done, we agree with Hogreve and Gremler (2009) that there remains key questions to be addressed related to service guarantees particularly how they can lead to improvements in internal service performance (e.g., process and employee enhancements and improvements in service delivery quality) and customer retention as well as their return on investment.…”
Section: Further Developments In the Academic Literaturementioning
confidence: 99%